(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The growth of the Internet has increased multi-folds in recent years. The Internet has become the medium of communication since the Covid-19 pandemic had started. The usage of communication via online means that the audio and visual content has also increased rapidly. Though it has been a boon for the major section of the people, differently-abled like the hearing-impaired people have limited resources to make use of. This project is aimed to design an application that converts the speech and text input into a sequence of sign language visuals. Speech recognition is used to convert the input audio to text and it is further translated into sign language. Natural Language Processing algorithms are used for word segmentation and extraction of root words. The translation happens to the Indian Sign Language in an effort to make this project more regional to the people of India.